GAMBARAN TINGKAT CAPAIAN TERAPI INSULIN PADA PASIEN RAWAT JALANDIABETES MELITUS TIPE 2 DI BAGIAN PENYAKIT DALAM RSUD ARIFIN ACHMAD PROVINSI RIAUPERIODE JANUARI – DESEMBER 2011 - Norra Purti Yolanda; Jazil Karimi; Dina Fauzia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Diabetes mellitus (DM) is a group of metabolic diseases, the characteristic is hyperglycemia that causes by abnormal of insulin secretion, insulin action or both of it. Insulin is a therapy of type 2 DM. Data of International Diabetes Federation showed that using insulin therapy in type 2 DM patient in Indonesia was classified low. This study aims to determine the description of the achievement insulin terapy level in type 2 DM patient’s. Design of this study is retrospective descriptive is done with and collect data from medical record to 114 type 2 DM patients who received combination oral antidiabetic agents with insulin therapy and intensive insulin therapy. The result of this research were found that combination oral antidiabetic agents with insulin therapy usage are higher than intensive insulin therapy is 77,2%. The most used combination therapy was combination long acting insulins with biguanids and sulfonylureas is 14,8%. The most used intensif insulin therapy was long acting insulin and rapid acting insulin is 38,4%. Achievement of therapeutic targets DM is 69,8% fasting blood glucose levels and 82,8% 2-hour postprandial blood glucose levels in bad catagory, 46% Triglycerides levels in avarege catagory, 64,2% HDL cholesterol in low catagory, 61,8% LDL cholesterol in bad catagory, 34% total cholesterol in bad catagory and 50% blood preassure in avarege catagory. Incidence of hypoglycemia is 7%. Conclusion of this study is the avhievement insulin therapy in type 2 diabetes mellitus patients is low catagory. Key words: insulin therapy, achievement of therapeutic targets